Phospholipids interaction with graphene and graphene oxide. At the interface of quantum calculations and practical experiment - Lanai, Victor (My University, 2023)
It has been shown that vertically grown graphene flakes are effective in killing bacteria, whilst keeping mammalian cells intact. It was also reported that the graphene oxide sheet can attach to certain drugs and thereby can be used as a therapeutic drug carrier for cancer treatment. However, there is lack of knowledge on the mechanism of interaction between different kinds of cells and graphene-based materials. Therefore, a deeper investigation into the interaction between graphene and the plasma membrane of different types of cells was undertaken. The cell membrane consists of two key components, phospholipids and proteins. Various types of phospholipids exist, and the different types are present in various organisms. Since the constituent of phospholipids seems to differ between bacteria, mammalian normal and cancerous cells, we choose phospholipids as the main target for this thesis. Six phospholipids were studied together with graphene and its derivative, graphene oxide. This thesis is divided into two parts, theoretical and practical parts. In the theoretical part, density functional theory (DFT) is utilized to enhance the understanding at a quantum level. Phospholipids are simulated as isolated single molecules, in pairs and together with graphene and graphene oxide. The theoretical calculations show that the most abundant phospholipids in mammalian cells have stronger bonding to each other, compared to bacterial phospholipids. Further, when the graphene/ graphene oxide sheet is approaching the phospholipid pairs, the bacterial pair exhibits less repulsive interactions, thereby a more stable system with the sheets was found. In the practical part, phospholipids were assembled into liposomes, mimicking a cell membrane and treated with fluorescein functionalized graphene oxide. With fluorescent microscope, we assessed the internalization of graphene oxide by liposomes. Furthermore, differential scanning calorimetry revealed that the constituent of phospholipids affects liposomes heat capacity, which is in line with the theoretical calculations. There would be some other interactions between the cells and approaching material, but we present phospholipids as the key player in this study.
Keywords: Phospholipids; graphene; graphene oxide; fluorescein; internalization; heat capacity; density functional theory